الرقابة الإدارية ودورها في تحسين الأداء الوظيفي لدى العاملين - بهناس, حفصة (My University, 2020)
The study aimed to identify administrative control and its role in improving the job performance of workers within the public hospital institution, by highlighting the control of workers and evaluating their performance, and highlighting the importance of administrative control as an important component of successful and effective management and its impact on increasing performance. The descriptive analytical approach was used for its suitability in the subject of the study, and the tool used to collect data was in the questionnaire, as it included a study of a sample of administrators at Sidi Ali Hospital to analyze the responses of individuals in a sample. Job performance evaluation is one of the most important control methods that increase the level of performance, which enables the organization to know the capabilities and competencies of its employees. The study recommended the need to raise the level of efficiency of the hospital’s management apparatus in the field of practicing administrative control and the necessity of increasing training courses for employees in the field of monitoring and evaluation in order to be acquainted with modern tools.
المؤسسة العمومية الاستشفائية "حمادو حسين" سيدي علي مستغانم
Keywords: administrative control، job performance،job performance evaluation، hospital public institution.